1996
DOI: 10.1002/art.1780391108
|View full text |Cite
|
Sign up to set email alerts
|

Autoreactivity to human heat‐shock protein 60 predicts disease remission in oligoarticular juvenile rheumatoid arthritis

Abstract: Objective. To determine whether T lymphocyte reactivity to endogenous human hsp60 plays a regulatory role in the course of oligoarticular juvenile rheumatoid arthritis (JRA).Methods. A prospective, longitudinal study of T cell reactivity to HSP in 15 patients with newly diagnosed HLA-B27 negative oligoarticular JRA was performed. Results were compared with those in a group of 20 patients with newly diagnosed polyarticular or systemic JRA or with acute arthritis caused by other systemic diseases or viral infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
53
0
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(59 citation statements)
references
References 26 publications
4
53
0
2
Order By: Relevance
“…Recently, we found that a similar protective mechanism occurs upon immunization with Mt hsp70 (7). Moreover, T cell responses to human hsp60 have been associated with self-remitting forms of juvenile chronic arthritis (8).…”
mentioning
confidence: 85%
“…Recently, we found that a similar protective mechanism occurs upon immunization with Mt hsp70 (7). Moreover, T cell responses to human hsp60 have been associated with self-remitting forms of juvenile chronic arthritis (8).…”
mentioning
confidence: 85%
“…HSP immunisations have been shown to inhibit autoimmune disorders such as diabetes and arthritis both in animal models and in initial clinical trials in patients with chronic inflammatory disease. [5][6][7][8][9][10][11][12] Over the past years, several research groups have shown that HSP reactive T cells might play a role in this regulatory function and in the induction of anti-inflammatory cytokines in chronic inflammation.…”
mentioning
confidence: 99%
“…Second, in RA, as well as in juvenile idiopathic arthritis (JIA), Hsp60 of microbial origins as well as those of endogenous origins are targets of immune responses (26,27). In the spontaneous remitting form of JIA (oligoarticular JIA), T cells reactive to self Hsp60 at the onset of disease are associated with disease remission (28) and have a striking regulatory phenotype (29). In RA, T cells stimulated with human Hsp60 display a marked suppressive phenotype, compared with T cells stimulated with homologous mycobacterial Hsp65 (26).…”
mentioning
confidence: 99%